STEM Digital Collaboration to Enhance Critical Thinking Skills of Secondary School Students: A Literature Review - Fatqurhohman Fatqurhohman; Haerul Syam; Ratih Puspasari; Fathul Niam; Agus Miftakhus Surur (Ihsan Cahaya Pustaka, 2025)
This literature review explores the role of STEM digital collaboration in enhancing critical thinking skills among secondary school students. As global demands for higher-order cognitive abilities intensify, integrating digital tools within STEM education has emerged as a promising approach to foster interactive, collaborative, and contextually meaningful learning experiences. The review synthesizes recent empirical studies and theoretical perspectives, highlighting innovative pedagogical models such as STEM-Blended Learning, Project-Based Learning, and STEM-based digital modules that effectively cultivate critical thinking. Notably, this study advances the understanding of how balanced technology integration, coupled with collaborative STEM activities, optimizes cognitive skill development while mitigating risks of overdependence on digital resources. The novelty of this review lies in its comprehensive focus on digital collaboration as a catalyst for critical thinking enhancement, bridging theoretical frameworks and practical applications in diverse secondary education contexts. Implications for educators and policymakers emphasize the strategic adoption of integrated STEM-digital pedagogies to prepare students for complex 21st-century challenges. Future research directions include evaluating cross-cultural effectiveness and addressing implementation barriers in technology-supported STEM collaboration.